28. ASSESSMENT OF THE TRAINING OF SOME CORE COMPETENCIES OF MASTERS OF NURSE IN VIETNAM (Vietnam Journal of Community Medicine, 2023)
Objectives: To evaluate the training of some core competencies of the master of nursing in Vietnam.Subjects and Methods: 240 masters of nursing were enrolled in a cross-sectional and descriptivestudy with convenience sampling method. These nurses autofilled the survey form on google formin order to evaluate their training in core competencies based on a 5-point Likert scale with 4 groupsof core competencies (Nursing professional competency; nursing management and professionaldevelopment; practice - making legal policy and professional ethics; and training and scientificresearch).Results: According to the respondents, 4 groups of core competencies with 38 specific skills hadhigh average score and passing rate. These 38 items in four groups of competencies were arrangedappropriately, meeting the requirements of high internal consistency.Conclusion: The content related to 4 groups of research competencies and 38 detailed competencieshas been taught in the master’s programs with different degrees, but not yet clearly specified for eachindividual content. Therefore, the groups of core and detailed competencies should be included in theoutput standards of the master’s degree nursing training program.
Keywords: Master of nursing; core competency.